PENGEMBANGAN DIGITAL LIBRARY SEBAGAI SUMBER BELAJAR - Robinson Situmorang, Cecep Kustandi (Perspektif Ilmu Pendidikan, 2013)
In the era of information and communication technology (ICT) every institution, including library, competes in integrating technology to develop and empower ICT based application in the library containing digital learning resource. This research focused on developing Digital Library as a students’ learning resource to assist them to search digital information. Applying ADDIE Model, the research took place at Curriculum and Educational Technology Program, The School of Education, The State University of Jakarta, in March – September 2012 following the steps: analysing the students’ need, designing, developing, implementing, and evaluating the product. The result of the development of the application database for the digital library is the the development of open source which has applied International Standard, AACR. The software is called SliMS (Senayan Library Management System). SliMS is an Open Source Software (OSS) web based and designed specifically to meet the need for library automation at small to big scales. Digital Library of Curriculum and Educational Technology Program, The School of Education, The State University of Jakarta is beneficial for the staff and students in searching references and instrucional materials.